IMAM NAWAWI'S OPINION ON THE RULING OF LIHURMATIL WAQTI PRAYER - Muhammad Syaifuddin Alfaruq; Ahmad Fais; Fahrudin Nafi’an; Ali As’ad (STAI Sebelas April Sumedang, 2025)
Ikhtilaf Ulama' Fiqh regarding legal ijtihad. The lihurmatil Waqti prayer raises a question mark among ordinary people, because they assume that when they have performed the lihurmatil Waqti prayer, they are not burdened with the obligation to pray I'adah. The Lihurmatil Waqti prayer is a prayer that is performed with the aim of respecting the entry of prayer time, because he performs the prayer in imperfect conditions (does not meet the requirements and harmony). The method used in this research is a qualitative method, using a narrative descriptive approach. Data collection in this research used the interview method and library research. The results of this research are four reasons that allow performing the Lihurmatil Waqti prayer, namely, Faqdut Thoharoyni, serious illness, travelers, and people who are in detention. The law of the Lihurmatil Waqti Prayer I'adah has been expressed by Imam Nawawi Al Bantani in the Book of Nihayatuz Zain, where his opinion is supported by the opinion of Imam Nawawi and Imam Hanbali, where the majority of Indonesia's population is of the Shafi'i faith.